Investigation of L-myc (T3109G) gene polymorphism in predicting of toxic complications risk in non-hodgkin's lymphomas treatment - Салах, Абушанаб А. А.; Выдыборец, Станислав Владимирович; Горовенко, Наталия Григорьевна; Гартовская, Ирина Радомировна; Кирьяченко, Светлана Петровна; Россоха, Зоя Ивановна (ScienceRise: Medical Science, 2016)
Aim of research. To define the influence of polymorphic variants of L-myc (T3109G) gene on the risk of development of hematological and non-hematological toxicity at polychemotharapy in patients with the different forms of non-hodgkin’s lymphomas. Methods. Patients with diffuse-macrocellular and microcellular lymphomas underwent 4 courses of polychemotherapy according to the nosologic forms of disease and treatment protocol. The clinical course of disease was assessed paying attention to the toxic effects and response on the therapy. The clinical-laboratory parameters in the period of disease manifestation were analyzed in details. All patients underwent the molecular-genetic examination of polymorphic variants of L-myc (T3109G) gene. Using the statistical analysis was assessed the influence of polymorphic variants of gene on the risk of development of toxic effects and the interconnection with clinic-laboratory parameters.. Results. The studies of the influence of polymorphic variants of L-myc (T3109G) gene on the risk of development of hematological and non-hematological toxicity at PCT at the different forms of NHL proved that the summary frequency of detection of the clinical cases of hematological and non-hematological toxicity did not differ in patients with DMCL and MCL and was not associated with polymorphism of the studied gene. Polymorphism of L-myc (T3109G) gene determined the spread of the tumor process, the risk of development of II-IV stages of disease that were detected more frequently at 3109ТG and 3109GG genotypes; and the 3109GG genotype was associated with the loss of body weight and the rise of the number of erythrocytes in the period of disease manifestation before the beginning of PCT courses. The risk of development of nephrological toxicity at chemotherapy in patients with NHL was associated with 3109ТG and 3109GG genotypes on L-myc gene. The number of toxic effects and the features of their combination in examined patients were not connected with polymorphism of L-myc (T3109G) gene. Conclusions. The further studies are needed for elaboration of the therapeutic-preventive arrangements on the decrease of risk of nephrological toxicity in patients with non-hodgkin’s lymphomas at polychemotherapy courses